PELATIHAN PENGEMBANGAN PEMBELAJARAN DIGITALISASI DI ERA SOCIETY 5.0 - Erni Suryati Pihung; Ni Nyoman Padmawati (LPPM Universitas PGRI Mahadewa Indonesia, 2022)
can be interpreted as a human-centered and technology-based learning concept. Educators have autonomy in choosing learning strategies to create active learning. The involvement of teachers and students in the learning process by exploring, discovering, discussing, critical thinking, and innovation in the use of technology. One good and effective solution is to use the whatsapp application and also eduppazle-based media. The purpose of this article is to explain the role of using the whatsapp application and also edpuzzle media in developing learning later that can be used by teachers in the learning process in the classroom so that learning is more fun. The writing of this article uses the literature study method by reviewing journals related to the whatsapp application and also the edpuzzle media. The results of this study are the use of WhatsApp applications and also edpuzzle-based media that can be applied in the world of education and can produce students who actively explore, discuss, think critically, and innovate.